High-strength hot-dip galvanized steel sheet and method for producing same

By controlling the dew point and corrosive gas concentration in the atmosphere in the annealing furnace, a high-strength hot-dip galvanized steel plate with excellent coating appearance and excellent coating adhesion during strong processing is achieved in a fully radiant tube heating furnace, which solves the problem of difficulty in controlling the coating in the prior art and improves the strength and corrosion resistance of the steel plate.

CN119731351APending Publication Date: 2025-03-28JFE STEEL CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380063090.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-07
Filing Date
2023-08-31
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the prior art, it is difficult to produce high-strength hot-dip galvanized steel plates with excellent coating appearance and coating adhesion during strong processing in a fully radiant tube type heating furnace, especially on steel plates containing oxidizing elements such as Si and Mn.

Method used

By controlling the dew point and corrosive gas concentration in the atmosphere in the annealing furnace, the steel plate is ensured to undergo internal oxidation within a temperature range of above 700°C, and surface enrichment and external oxidation are suppressed, thereby optimizing the appearance and adhesion of the plating layer.

Benefits of technology

It realizes the high-strength hot-dip galvanized steel plate with excellent coating adhesion during strong processing, ensuring the high strength and corrosion resistance of the steel plate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

Provided is a method for producing a high-strength hot-dip galvanized steel sheet having, on the surface of a steel sheet that contains a prescribed component composition, a component composition in which the mass ratio of Si to Mn (Si / Mn) is 0.25 or more, and the remainder comprising Fe and unavoidable impurities, a galvanized layer in which the amount of deposited plating layer per surface is 20-120 g / m2, when annealing and hot-dip galvanizing are performed on a steel sheet in a continuous hot-dip galvanizing facility, the maximum temperature (T) of the steel sheet in an annealing furnace is 900 DEG C or less, and the dew point (X) of the atmosphere in the furnace in a temperature range in which the steel sheet temperature is 700-T DEG C is controlled to be equal to or greater than the dew point calculated by formula (1). The atmosphere in the heating furnace contains not only 3.0 vol% to 20.0 vol% of hydrogen but also 0.1 ppm to 3.0 ppm by volume of SO2 and / or 0.5 ppm to 10.0 ppm by volume of HCl, with the balance being nitrogen and unavoidable impurities. Dew point X > = (-50 + [Si mass%] * (T-600) / 30 + [Mn mass%] * (T-600) / 25) (1)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-strength galvanized steel sheet having excellent processability, which is more important as the tensile strength increases, and suitable for building materials and collision-resistant parts of automobiles, and a method for producing the same. Background Art

[0002] In today's world where there is a strong demand for improved collision safety and fuel efficiency of automobiles, steel sheets used as raw materials for parts are being made stronger. In addition, the popularity of automobiles is expanding worldwide, and automobiles are used for a variety of purposes in a variety of regions and climate conditions. In response to this, steel sheets used as raw materials for parts are required to have high rust resistance.

[0003] Generally, hot-dip galvanized steel sheets are manufactured by using a thin steel sheet obtained by hot rolling and cold rolling a steel billet as a base material and subjecting the base steel sheet to recrystallization annealing and hot-dip galvanizing treatment in an annealing furnace of a continuous hot-dip galvanizing line (hereinafter referred to as CGL). In the case of alloyed hot-dip galvanized steel sheets, alloying treatment is further performed after hot-dip galvanizing treatment.

[0004] Here, as the heating furnace types of the annealing furnace of CGL, there are direct fired furnace (DFF) type, non oxidizing furnace (NOF) type, radiation furnace (RTF) type, etc. In recent years, the construction of CGLs with full radiation tube type heating furnaces that make all heating furnaces radiation furnace type is increasing for reasons such as ease of operation and difficulty in pecking, etc., in which high-quality plated steel sheets can be manufactured at low cost. On the other hand, in the case of steel sheets containing easily oxidizable elements such as Si and Mn, it is preferred to oxidize under appropriate conditions immediately before reduction annealing. Unlike annealing furnaces in which direct fired furnaces and non oxidizing furnaces are configured in the front section of the annealing furnace, the full radiation tube type annealing furnace does not have an oxidation process immediately before reduction annealing. Therefore, for steel sheets containing easily oxidizable elements such as Si and Mn, it is disadvantageous in ensuring the coating properties.

[0005] As a method for manufacturing a hot-dip galvanized steel sheet using a high-strength steel sheet containing a large amount of Si and Mn as a base material, Patent Documents 1 and 2 disclose a technique for internally oxidizing the surface layer of the steel base by increasing the dew point in the heating process in the annealing furnace. However, the techniques described in Patent Documents 1 and 2 are difficult to control the dew point and to operate stably because the area for controlling the dew point is based on the entire furnace. In addition, when manufacturing alloyed hot-dip galvanized steel sheets based on unstable dew point control, the distribution state of the internal oxide formed in the base steel sheet is biased, and defects such as uneven coating wettability (deviation) and uneven alloying (deviation) may occur in the length direction and width direction of the steel sheet.

[0006] In addition, Patent Document 3 discloses the following technology: by not only specifying the concentration of H2O and O2 as oxidizing gases but also specifying the concentration of CO2, the surface layer of the steel base before coating is internally oxidized, external oxidation is suppressed, and the coating appearance is improved. However, in the case of containing a particularly large amount of Si as in Patent Document 3, due to the presence of internal oxides, cracks are easily generated on the surface of the base steel sheet during processing, and the coating peeling resistance is deteriorated. In addition, the corrosion resistance is also confirmed to be deteriorated. Furthermore, CO2 causes furnace contamination, carburization on the surface of the steel sheet, etc., and there are concerns about changes in mechanical properties.

[0007] In addition, recently, the application of high-strength hot-dip galvanized steel sheets and high-strength alloyed hot-dip galvanized steel sheets in parts that are subjected to severe processing (hereinafter referred to as strong processing) is being promoted, and the coating peeling resistance during strong processing has been paid attention to. Specifically, when the plated steel sheet is bent at more than 90°, bent at a more acute angle, or when an impact is applied or the steel sheet is processed, it is required to suppress the coating peeling of the processed part.

[0008] In order to satisfy such characteristics, it is not only necessary to add a large amount of Si to steel to ensure the desired steel sheet structure, but also it is required to have a higher level of control over the structure and structure of the steel base surface layer immediately below the coating layer, which may become the starting point of cracks during strong working. However, such control is difficult in the prior art, and it is impossible to manufacture hot-dip galvanized steel sheets with excellent coating adhesion during strong working using Si-containing high-strength steel sheets as base materials using CGLs equipped with a full-radiant tube heating furnace in an annealing furnace.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Japanese Patent Re-Publication No. 2014-102901

[0012] Patent Document 2: Japanese Patent Application No. 2014-525986

[0013] Patent Document 3: Japanese Patent Application Publication No. 2006-233333 Summary of the invention

[0014] Problems to be solved by the invention

[0015] The present invention has been completed in view of the above situation, and its purpose is to provide a high-strength hot-dip galvanized steel sheet and a manufacturing method thereof, which is manufactured in a CGL having a full-radiant tube heating furnace in an annealing furnace, uses a steel sheet containing Si and Mn as a base material, and has excellent coating appearance and coating adhesion during strong processing.

[0016] It should be noted that the high strength of the high-strength galvanized steel sheet of the present invention means that the tensile strength is 780 MPa or more.

[0017] Methods used to solve problems

[0018] From the perspective of ensuring the coating property, it is effective to set up an oxidation process before annealing in a heating furnace. However, there are problems with the coating peeling and corrosion resistance during processing, and from the perspective of cost and operability, it is urgently desired to ensure the coating property in a full-radiant tube heating furnace. In this regard, in the past, the dew point was increased only by increasing the water vapor partial pressure in the annealing furnace as a whole, so that the surface layer of the steel plate was internally oxidized. At this time, surface diffusion and surface oxidation (hereinafter also referred to as surface enrichment) of the easily oxidizable elements in the steel also occur during internal oxidation. Therefore, in order to ensure the appearance of the above-mentioned coating and the adhesion of the coating, it is necessary to efficiently suppress surface enrichment. Therefore, the inventors conducted in-depth research on the factors related to internal oxidation and surface enrichment, and found that it is extremely important to contain a trace amount of corrosive gases such as SO2 and HCl in the atmosphere during annealing, and then control the dew point in the temperature range above 700°C. In addition, the inventors investigated the necessary dew point at various steel plate annealing temperatures, and found that, when the maximum temperature of the steel plate in the atmosphere in the heating furnace is set to T°C, the maximum temperature T and the Si and Mn concentrations in the steel have a great influence on the oxidation (hereinafter sometimes referred to as internal oxidation) and surface enrichment of the surface layer of the steel plate within 100 μm from the surface of the base steel plate to the center of the plate thickness. In addition, it was found that, as a method for efficiently suppressing surface enrichment and performing the required oxidation in the surface layer of the steel plate within 100 μm from the surface of the base steel plate to the center of the plate thickness, specifically, it is effective to control the dew point X°C in the temperature range of 700°C to T°C (700°C < T ≤ 900°C) of the steel plate in the heating furnace until the maximum temperature T°C to be above the dew point calculated by the following formula (1).

[0019] Dew point X ≥ (-50 + [Si mass %] × (T-600) / 30 + [Mn mass %] × (T-600) / 25) … (1)

[0020] Here, the maximum temperature T°C of the steel plate in the atmosphere in the heating furnace is set to 900°C or less because, when the maximum temperature T°C exceeds 900°C, it is difficult to suppress the surface enrichment of Si and Mn, and internal oxidation also becomes excessive, thereby reducing the surface appearance and the adhesion of the coating during processing.

[0021] By performing such treatment, selective surface oxidation can be suppressed, surface enrichment can be suppressed, and a high-strength hot-dip galvanized steel sheet with excellent coating appearance and coating adhesion during strong processing can be obtained. It should be noted that excellent coating appearance means that the coating has an appearance where no non-coating or uneven alloying is confirmed.

[0022] The structure of the high-strength hot-dip galvanized steel sheet obtained by the above method is as follows: the oxygen content of the steel sheet surface within 100 μm from the surface of the base steel sheet immediately below the galvanized layer is 0.030 g / m per single side. 2 Above and 0.40g / m 2 Furthermore, the maximum length of the oxides present in the surface layer of the steel plate is 6.0 μm or less, and the number of oxides present in the surface layer of the steel plate having a length of 1.0 μm or more is 20 or less per 100 μm length in the width direction of the steel plate of the surface layer of the steel plate. This can achieve stress relaxation and crack prevention during bending of the steel base surface layer, and excellent coating appearance and coating adhesion during strong processing.

[0023] The present invention is based on the above findings, and its features are as follows.

[0024] [1] A method for producing a high-strength hot-dip galvanized steel sheet, comprising producing a steel sheet having a coating weight of 20 g / m2 per single surface on the surface of the steel sheet containing, by mass%, C: 0.08% or more and 0.25% or less, Si: 0.1% or more and less than 2.0%, Mn: 1.5% or more and 3.5% or less, P: 0.02% or less, S: 0.01% or less, Al: 0.10% or less, N: 0.006% or less, a mass ratio of Si to Mn (Si / Mn) of 0.25 or more, and the balance being Fe and unavoidable impurities. 2 Above and 120g / m 2A method for producing a high-strength hot-dip galvanized steel sheet with a zinc coating as follows, wherein when the steel sheet is annealed and hot-dip galvanized in a continuous hot-dip galvanizing facility, the maximum temperature T of the steel sheet in the annealing heating furnace is 900°C or less, the dew point X (°C) of the atmosphere in the heating furnace within a temperature range where the steel sheet temperature is 700°C or more and T°C or less is controlled to be above the dew point calculated using the following formula (1), and the atmosphere in the heating furnace contains, in addition to 3.0% by volume and 20.0% by volume of hydrogen, at least one of 0.1% by volume ppm and 3.0% by volume ppm of SO2 and 0.5% by volume ppm and 10.0% by volume ppm of HCl, with the remainder being nitrogen and impurities.

[0025] Dew point X ≥ (-50 + [Si mass %] × (T-600) / 30 + [Mn mass %] × (T-600) / 25) … (1)

[0026] Here, Si mass % is the mass % of Si in the component composition of the steel plate, and Mn mass % is the mass % of Mn in the component composition of the steel plate.

[0027] [2] The method for producing a high-strength hot-dip galvanized steel sheet according to [1], wherein the steel sheet further contains, in terms of mass %, one or more members selected from the following groups A to E.

[0028] Group A: one or more of Ti, Nb, V and Zr with a total content of less than 0.2%;

[0029] Group B: one or more of Mo, Cr, Cu and Ni in a total amount of 0.01% to 0.5%;

[0030] Group C: B with a value of more than 0.0003% and less than 0.005%;

[0031] Group D: one or more of Sb and Sn in a total amount of 0.001% or more and 0.2% or less;

[0032] Group E: One or more of Ca, Mg, and REM in an amount of 0.0001% to 0.0005% in total.

[0033] [3] A high-strength hot-dip galvanized steel sheet having a coating weight of 20 g / m2 per single surface on a surface of the steel sheet comprising, by mass%, C: 0.08% or more and 0.25% or less, Si: 0.1% or more and less than 2.0%, Mn: 1.5% or more and 3.5% or less, P: 0.02% or less, S: 0.01% or less, Al: 0.10% or less, N: 0.006% or less, a mass ratio of Si to Mn (Si / Mn) of 0.25 or more, and the balance being Fe and unavoidable impurities. 2 Above and 120g / m2 The following galvanized layers,

[0034] The oxygen content of the steel sheet surface within 100 μm from the surface of the base steel sheet to the center of the thickness immediately below the galvanized layer is 0.030 g / m per single side. 2 Above and 0.40g / m 2 Hereinafter, the maximum length of the oxides existing in the surface layer of the steel plate is less than 6.0 μm, and the number of oxides having a length of 1.0 μm or more existing in the surface layer of the steel plate is less than 20 per 100 μm length of the surface layer of the steel plate in the width direction of the steel plate.

[0035] [4] The high-strength hot-dip galvanized steel sheet according to [3], wherein the steel sheet further contains, in terms of mass %, one or more members selected from the following groups A to E.

[0036] Group A: one or more of Ti, Nb, V and Zr with a total content of less than 0.2%;

[0037] Group B: one or more of Mo, Cr, Cu and Ni in a total amount of 0.01% to 0.5%;

[0038] Group C: B with a value of more than 0.0003% and less than 0.005%;

[0039] Group D: one or more of Sb and Sn in a total amount of 0.001% or more and 0.2% or less;

[0040] Group E: One or more of Ca, Mg, and REM in an amount of 0.0001% to 0.0005% in total.

[0041] Effects of the Invention

[0042] According to the present invention, a high-strength hot-dip galvanized steel sheet having excellent coating appearance and coating adhesion during intensive processing can be obtained. DETAILED DESCRIPTION

[0043] Hereinafter, embodiments of the present invention will be described. However, the present invention is not limited to the following embodiments.

[0044] First, the annealing atmosphere conditions that determine the structure of the surface of the base steel sheet immediately below the coating layer, which are the most important elements in the present invention, will be described.

[0045] In the heating process of annealing in the continuous hot-dip galvanizing facility, the dew point X (°C) of the atmosphere in the temperature range of the steel sheet temperature in the heating furnace is controlled to be above the dew point calculated by the following formula (1). Here, T°C is the maximum temperature of the atmosphere in the annealing furnace, which is 700°C < T ≤ 900°C.

[0046] Dew point X ≥ (-50 + [Si mass %] × (T-600) / 30 + [Mn mass %] × (T-600) / 25) … (1)

[0047] In order to perform recrystallization treatment of the strain imparted by the cold rolling that is usually performed, the maximum temperature of the steel sheet during the heating process of annealing needs to exceed 700°C. On the other hand, if it exceeds 900°C, it is difficult to suppress the surface enrichment of Si and Mn, and the oxidation of the surface layer of the steel sheet within 100 μm from the surface of the base steel sheet to the center of the plate thickness becomes excessive, which reduces the surface appearance and the adhesion of the coating during processing. Therefore, the maximum temperature of the steel sheet needs to be more than 700°C and less than 900°C.

[0048] The control range of the atmosphere dew point X in the temperature range of 700° C. or higher and T° C. or lower (700° C. < T ≤ 900° C.) during heating will be described.

[0049] In terms of suppressing surface oxides, it is most important to control the dew point at a steel plate temperature of 700°C or above, where the diffusion rate of elements increases. At this time, in order to efficiently internally oxidize Si and Mn and suppress surface enrichment, it is necessary to control the dew point X in the temperature range of 700°C or above to the dew point range specified by the above formula (1). When the dew point X is lower than this range, the suppression of surface enrichment becomes insufficient, which will lead to a decrease in the appearance of the coating and the adhesion of the coating. There is no particular upper limit on the dew point, but when the dew point is too high, the operating cost of the humidification equipment also increases, so it is preferably below +20°C, and more preferably below +5°C.

[0050] Here, in the temperature range below 700°C, due to the low temperature, the surface diffusion of easily oxidizable elements such as Si and M is very small, and surface enrichment is suppressed (or does not occur). Therefore, the wettability of molten zinc and steel sheets is not hindered. Therefore, dew point control is required in the temperature range above 700°C.

[0051] The atmosphere in the heating furnace during annealing needs to be set to a hydrogen concentration of 3.0 volume % or more and 20.0 volume % or less. When the hydrogen concentration in the heating furnace atmosphere in the temperature range above 700°C is too high, the amount of diffusible hydrogen in the steel becomes too high, and there is a problem of hydrogen embrittlement and damage to workability. On the other hand, when the hydrogen concentration in the heating furnace atmosphere is too low, the reduction of the steel plate surface becomes insufficient and inert, and there is a problem of poor plating, so it is necessary to set the hydrogen concentration in the temperature range above 700°C to 3.0 volume % or more and 20.0 volume % or less.

[0052] The atmosphere in the heating furnace during annealing needs to contain at least one of SO2 of 0.1 volume ppm or more and 3.0 volume ppm or less and HCl of 0.5 volume ppm or more and 10.0 volume ppm or less. Although the detailed reason is still uncertain, it is speculated that in the presence of an appropriate amount of these corrosive gases, compared with the oxidation of the surface of Si and Mn, the internal oxidation is promoted, the coating adhesion is improved, and not only that, the length of the oxide present in the surface layer of the steel plate described later is reduced, and the corrosion resistance after processing is improved. The improvement effect brought by these corrosive gases is significant when SO2 is 0.1 volume ppm or more and HCl is 0.5 volume ppm or more, but when SO2 exceeds 3.0 volume ppm and HCl exceeds 10.0 volume ppm, it is possible to promote the deterioration of the furnace body in the heating furnace. Therefore, it is necessary to set SO2 to 0.1 volume ppm or more and 3.0 volume ppm or less, and set HCl to 0.5 volume ppm or more and 10.0 volume ppm or less. In addition, the balance of the atmosphere in the heating furnace during annealing is nitrogen and impurities. Even if CO, CO2, etc. are contained as impurities, the effect will not be impaired, and these gases may be contained.

[0053] The concentration of these trace amounts of corrosive gases such as SO2 and HCl can be controlled by adjusting the amount of gas containing these corrosive gases directly introduced into the furnace. In addition, it can also be controlled by applying a liquid containing H2SO4 and HCl on the steel plate before entering the furnace and then diluting the liquid with water. In short, it is important to control the concentration of trace amounts of corrosive gases such as SO2 and HCl, and the method for controlling the concentration of these trace amounts of corrosive gases such as SO2 and HCl is not limited to the above method.

[0054] Next, the steel component composition of the high-strength hot-dip galvanized steel sheet to which the present invention is directed will be described. The composition is expressed in mass %.

[0055] C: 0.08% or more and 0.25% or less

[0056] C is an element effective for high strength of steel plate, and contributes to high strength by forming martensite, which is one of the hard phases of steel structure. In addition, according to the manufacturing method, it also contributes to high strength by forming fine alloy compounds or alloy carbonitrides with carbide-forming elements such as Nb, Ti, V, and Zr. In order to obtain these effects, the C content needs to be set to 0.08% or more. On the other hand, when the C content exceeds 0.25%, the martensite is over-hardened, and there is a tendency that the bending workability will not be improved even if the inclusions and hydrogen content in the steel are controlled. Therefore, the C content is set to 0.08% or more and 0.25% or less. From the viewpoint of making TS stably above 780MPa, the C content is preferably 0.09% or more.

[0057] Si: 0.1 or more and less than 2.0%

[0058] Si is an element that mainly contributes to high strength through solid solution strengthening. Compared with the increase in strength, the reduction of ductility is relatively small, which not only contributes to strength but also contributes to the balance between strength and ductility. The improvement of ductility brings about the improvement of bendability. On the other hand, Si easily forms Si-based oxides on the surface of the steel sheet, which sometimes becomes the reason for not being plated, and when contained in excessive amounts, a significant scale is formed during hot rolling and the surface of the steel sheet has scale defects, and sometimes the surface properties deteriorate. Therefore, the amount required for ensuring strength is added, and the lower limit is set to more than 0.1%. From the viewpoint of coating property, the upper limit is set to less than 2.0%. Preferably, it is less than 1.8%.

[0059] Mn: 1.5% or more and 3.5% or less

[0060] Mn is effective as an element that contributes to high strength through solid solution strengthening and martensite formation. In order to obtain this effect, it is necessary to contain more than 1.5%. Preferably, it is more than 1.8%. On the other hand, when it exceeds 3.5%, it is easy to produce unevenness in the steel structure due to the segregation of Mn, resulting in a decrease in workability. In addition, Mn is easily oxidized externally as an oxide or a composite oxide on the surface of the steel plate, which sometimes becomes the reason for not being plated. Therefore, the upper limit is set to 3.5%.

[0061] P: 0.02% or less

[0062] P is an effective element that contributes to the high strength of steel plate by solid solution strengthening. On the other hand, it has an impact on the coating property. Especially, it causes the deterioration of the wettability of the steel plate and the delay of the alloying speed of the coating, and has a great impact in obtaining a high alloy system such as a high-strength steel plate. Therefore, the upper limit is set to 0.02%. More preferably, it is below 0.01%. The lower limit is not particularly specified, but when it is less than 0.0001%, it causes a reduction in production efficiency and an increase in dephosphorization cost during the manufacturing process, so it is preferably set to more than 0.0001%.

[0063] S: 0.01% or less

[0064] S easily forms sulfide-based inclusions in steel. In particular, when a large amount of Mn is added for high strength, MnS-based inclusions are easily formed. In addition to being a cause of impairing bendability, S becomes a cause of hot brittleness and has an adverse effect on the manufacturing process, so it is preferably reduced as much as possible. In the present invention, up to 0.01% is allowed. The lower limit is not particularly specified, but when it is less than 0.0001%, it leads to reduced production efficiency and increased costs in the manufacturing process, so it is preferably set to 0.0001% or more.

[0065] Al: 0.10% or less

[0066] Al is added as a deoxidizing material. In order to obtain this effect, it is preferably contained at least 0.001%. On the other hand, when the Al content exceeds 0.10%, inclusions are easily formed during the manufacturing process, which deteriorates the bendability. Therefore, Al is preferably less than 0.10%, preferably less than 0.08% in terms of sol.Al in steel.

[0067] N: 0.006% or less

[0068] When the N content exceeds 0.006%, excessive nitrides are generated in the steel, which reduces the workability and sometimes leads to deterioration of the surface properties of the steel sheet. Therefore, N is set to 0.006% or less, preferably 0.005% or less. From the viewpoint of cleaning the microstructure and improving ductility, the N content is preferably as small as possible, but since it leads to reduced production efficiency and increased costs in the manufacturing process, the lower limit of N is set to 0.0001% or more.

[0069] The above-mentioned component composition may contain the following components as optional components. In addition, when the following optional elements are contained in an amount less than the following lower limit, the optional components are contained as unavoidable impurities.

[0070] In terms of mass %, at least one member selected from the following groups A to E is contained

[0071] Group A: one or more of Ti, Nb, V and Zr with a total content of less than 0.2%;

[0072] Group B: one or more of Mo, Cr, Cu and Ni in a total amount of 0.01% to 0.5%;

[0073] Group C: B with a value of more than 0.0003% and less than 0.005%;

[0074] Group D: one or more of Sb and Sn in a total amount of 0.001% or more and 0.2% or less;

[0075] Group E: One or more of Ca, Mg, and REM in an amount of 0.0001% to 0.0005% in total.

[0076] Ti, Nb, V and Zr form carbides and nitrides (sometimes carbonitrides) with C and N. By forming fine precipitates, it helps to increase the strength of the steel plate. In particular, by precipitating in soft ferrite, its strength is improved, and by reducing the strength difference with martensite, it helps to improve the stretch flangeability in addition to improving the bendability. In addition, these elements have the effect of refining the structure of the hot-rolled coil, and by refining the steel structure after subsequent cold rolling and annealing, it also helps to increase the strength and improve the processability such as bendability. From the viewpoint of obtaining this effect, it is preferred to contain more than 0.005% of Ti, Nb, V and Zr in total. However, excessive addition not only increases the deformation resistance during cold rolling and hinders productivity, but the presence of excessive or coarse precipitates reduces the ductility of ferrite, and reduces the ductility and bendability of the steel plate. Therefore, the upper limit of the total of more than one of Ti, Nb, V and Zr is set to 0.2%.

[0077] Mo, Cr, Cu and Ni are elements that improve hardenability and easily generate martensite, so they contribute to high strength. In order to obtain these effects, it is preferred to contain more than one of Mo, Cr, Cu and Ni in a total of 0.01%. For Mo, Cr, Cu and Ni, their excessive addition not only leads to saturation of the effect and increased cost, but also, for Cu, induces cracks during hot rolling and becomes the cause of surface defects. Therefore, it is preferred that more than one of Mo, Cr, Cu and Ni is set to a total of less than 0.5%. It should be noted that for Ni, since it has the effect of suppressing the generation of surface defects caused by Cu addition, it is preferably added simultaneously when Cu is added. In particular, it is preferred that Ni contains more than 1 / 2 of the amount of Cu.

[0078] B is also an element that improves hardenability and makes martensite easy to form, thus contributing to high strength. For B, in addition to setting a lower limit for obtaining the inhibitory effect of ferrite formation occurring during annealing cooling, even if excessively added, the high strength effect is saturated, and on the contrary, the hardenability becomes excessive, resulting in unfavorable factors such as weld cracks during welding, so an upper limit is set. Therefore, when B is contained, the content is preferably set to 0.0003% or more and 0.005% or less.

[0079] Sb and Sn inhibit decarburization, denitrification, deboronization, etc., and are effective elements for inhibiting the strength reduction of the steel sheet, so it is preferred to contain one or more of Sb and Sn in a total of 0.001% or more. However, excessive addition degrades the surface properties, so it is preferred to set the upper limit to a total of one or more of 0.2% or less.

[0080] If a small amount of Ca, Mg and REM is added, the shape of the sulfide is spherical, which has the effect of improving the bendability of the steel sheet. On the other hand, if excessively added, excessive sulfides and oxides are formed in the steel, which reduces the workability, especially the bendability, of the steel sheet. Therefore, it is preferable to set the total amount of one or more of Ca, Mg and REM to 0.0005% or less. In addition, the lower limit of the content is not particularly specified, but it is preferable to contain one or more of Ca, Mg and REM in a total amount of 0.0001% or more.

[0081] The mass ratio of Si to Mn (Si / Mn) is 0.25 or more

[0082] In order to obtain excellent plating properties, it is important to control the easily oxidizable elements in the steel. From the perspective of suppressing the external oxidation of Mn, it is necessary to form SiMn composite oxides inside the steel sheet. When the Si / Mn ratio is less than 0.25, a sufficient amount of SiMn composite oxides are not formed in the surface layer of the steel sheet within 100 μm from the surface of the base steel sheet, and surface enrichment occurs, resulting in poor plating. Therefore, the Si / Mn ratio is set to 0.25 or more.

[0083] In addition, the balance is Fe and inevitable impurities.

[0084] The high-strength galvanized steel sheet of the present invention has a coating weight of 20 g / m2 per single surface on the surface of the steel sheet. 2 Above and 120g / m 2 The zinc coating is less than 20g / m 2 On the other hand, when the thickness exceeds 120 g / m 2 When the coating is thicker, the adhesion of the coating deteriorates.

[0085] In addition, the oxygen content of the surface layer of the steel sheet within 100 μm from the surface of the base steel sheet to the center of the sheet thickness immediately below the galvanized layer measured by the method described in the examples is 0.030 g / m per single side. 2 Above and 0.40g / m 2 From the viewpoint of obtaining fine oxides, the oxide containing oxygen preferably has at least one element selected from Fe, Si, Mn, Al, P, B, Nb, Ti, Cr, Mo, and V as a main component. In addition, the maximum length of the oxide present in the surface layer of the steel plate is 6.0 μm or less, and the number of grain boundary internal oxides with a length of 1.0 μm or more present in the surface layer of the steel plate is 20 or less per 100 μm length in the width direction of the steel plate of the surface layer of the steel plate.

[0086] For hot-dip galvanized steel sheets in which Si and a large amount of Mn are added to the steel, in order to satisfy the requirements of good appearance and coating adhesion during processing, it is necessary to control the amount and size of oxides in the steel base surface layer immediately below the coating, which may become the starting point of cracks during strong processing. Therefore, in the present invention, in the annealing process described later, dew point control is performed to control the oxygen potential. As a result, the oxygen potential becomes higher, and Si, Mn, etc., which are easily oxidizable elements, undergo internal oxidation before plating. As a result, the activity of Si and Mn in the surface layer of the steel base is reduced, while external oxidation is suppressed, resulting in improved coating appearance and adhesion. The improvement effect is achieved when the oxygen content of the steel plate surface layer within 100 μm from the surface of the base steel plate is 0.030 g / m per single side. 2 The lower limit is set to 0.030 g / m per side. 2 On the other hand, even if the oxygen content exceeds 0.40 g / m 2 Even if the effect is saturated, and it may cause cracks during strong processing in some cases, the upper limit is set to 0.40 g / m 2 .

[0087] The conditions of the oxide present in the surface layer of the steel plate that becomes the starting point of cracks were investigated, and it was found that the oxide present in the surface layer of the steel plate with an oxide width of more than 0.1 μm and a length of more than 1.0 μm contributes to cracks, and the greater the length, the more significant the crack effect. Therefore, the maximum length of the oxide present in the surface layer of the steel plate is set to be less than 6.0 μm. When the oxide length exceeds 6.0 μm, the oxide becomes the starting point of cracks during processing, and the adhesion and corrosion resistance after processing are significantly deteriorated. On the other hand, the oxide that satisfies either a width of less than 0.1 μm or a length of less than 1.0 μm has little effect on cracks during strong processing, so it does not affect the adhesion and corrosion resistance after processing. The lower limit of the maximum length of the oxide present in the surface layer of the steel plate is not particularly specified, and is about 0.3 μm in the method of the present invention, preferably 0.3 μm or more.

[0088] In addition, among the oxides present in the surface layer of the steel plate, the number of internal oxides having a length of 1.0 μm or more is set to be 20 or less per 100 μm length in the width direction of the steel plate at the surface layer of the steel plate. When the number of internal oxides having a length of 1.0 μm or more exceeds 20 per 100 μm length in the width direction of the steel plate at the surface layer of the steel plate, the internal oxides become the starting point of cracks during processing, and the adhesion and corrosion resistance after processing are deteriorated, just like when the maximum length of the oxide exceeds 6.0 μm. Therefore, the number of internal oxides having a length of 1.0 μm or more is set to be 20 or less per 100 μm length in the width direction of the steel plate at the surface layer of the steel plate. There is no special lower limit, but when it is less than 4, it is difficult for the oxygen content of the surface layer of the steel plate to meet 0.030 g / m per single side. 2, so it is preferably 4 or more.

[0089] Next, the method for producing the high-strength galvanized steel sheet of the present invention is described. The method for producing the high-strength galvanized steel sheet of the present invention comprises a casting step, a hot rolling step, a pickling step, a cold rolling step, an annealing step, and a galvanizing step. Each step is described below.

[0090] The casting step is a step of casting the steel having the above-mentioned chemical composition under the condition that the flow rate of molten steel at the solidification interface near the meniscus of the mold is 16 cm / sec or more to produce a steel material.

[0091] Steel raw material (steel billet (cast sheet)) manufacturing

[0092] The steel used in the manufacturing method of the present invention uses steel generally called a steel slab manufactured by a continuous casting method in order to prevent macrosegregation of alloy components. The steel may be manufactured by an ingot casting method, a thin slab casting method, or the like.

[0093] From the viewpoint of controlling inclusions, when continuous casting is performed, the casting is performed under the condition that the flow rate of molten steel at the solidification interface near the meniscus of the mold is 16 cm / sec or more. "Near the meniscus of the mold" refers to the interface between the powder and the molten steel used in the continuous casting in the mold. In the case of ingot casting, it is preferred to make the inclusions fully float during solidification and discard the floating and collected parts for the next process.

[0094] The hot rolling process is a process of hot rolling the steel material after the casting process.

[0095] In addition to the existing method of temporarily cooling the steel billet to room temperature and then reheating it after manufacturing, there is also a method of loading the steel billet into a heating furnace for hot rolling in a warm state without cooling it to near room temperature, a method of hot rolling immediately after a small amount of supplementary heating, or a method of hot rolling while maintaining a high temperature after casting.

[0096] The hot rolling method is not particularly limited, but is preferably performed under the following conditions.

[0097] The heating temperature of the steel billet is preferably set to a range of 1100°C or more and 1350°C or less. This is because the precipitates that may exist in the steel billet are prone to coarsening, which may be disadvantageous in ensuring strength by precipitation strengthening, or the coarse precipitates may be used as nuclei to adversely affect the microstructure formation in the subsequent annealing process. In addition, it is beneficial to reduce cracks and unevenness on the surface of the steel plate by heating, and to achieve a smooth surface of the steel plate as a product quality. From this point of view, the heating temperature of the steel billet is specified. In order to obtain such an effect, the heating temperature of the steel billet is preferably set to 1100°C or more. On the other hand, when the heating temperature of the steel billet exceeds 1350°C, the coarsening of the austenite grains occurs, and the steel structure of the final product is also coarsened, which becomes the reason for reducing the strength and bendability of the steel plate. Therefore, as the preferred upper limit of the heating temperature of the steel billet, 1350°C or less is specified.

[0098] In the hot rolling process including rough rolling and finish rolling, the steel billet is usually converted into a thin slab by rough rolling and into a hot rolled coil by finish rolling. However, this is not limited to the division depending on the rolling mill capacity, and there is no problem as long as the predetermined size is achieved.

[0099] As hot rolling conditions, the following conditions are recommended.

[0100] Finishing temperature: 800°C or higher and 950°C or lower

[0101] By setting the finishing temperature to 800°C or above, the goal is to obtain a uniform structure from the hot rolled coil and a uniform structure for the final product. When the structure is not uniform, the bendability is reduced. On the other hand, when the finishing temperature exceeds 950°C, the amount of oxide (scale) generated increases, the interface between the steel base and the oxide becomes rough, and the surface quality after pickling and cold rolling deteriorates. In addition, the crystal grain size becomes coarse, so as when the structure of the steel billet is coarsened, it becomes a cause of reducing the strength and bendability of the steel plate.

[0102] In order to make the structure finer and more uniform, the hot-rolled coil (hot-rolled plate) that has completed the above-mentioned hot rolling is preferably cooled within 3 seconds after the end of the finish rolling, cooled at an average cooling rate of 10 to 250°C / s in the temperature range of [finishing rolling temperature] to [finishing rolling temperature - 100]°C, and coiled into a coil in the temperature range of 450 to 700°C.

[0103] The pickling process is a process of pickling the steel sheet after the hot rolling process. The pickling removes the oxide scale from the surface of the steel sheet. The pickling conditions can be appropriately set.

[0104] The cold rolling process is a process of cold rolling the steel sheet after the pickling process.

[0105] The cold rolling reduction rate is preferably 20% or more and 80% or less. By setting the reduction rate to 20% or more, a uniform and fine steel structure can be obtained in the subsequent annealing process, so the reduction rate is preferably 20% or more. When the cold rolling reduction rate is less than 20%, it is easy to become coarse grains during annealing and easy to become an uneven structure, so as mentioned above, there is a concern that the strength and processability of the final product will be reduced. For the upper limit, a high reduction rate sometimes leads to poor shape in addition to the reduction in productivity caused by the rolling load, so the reduction rate is preferably set to 80% or less. It should be noted that pickling can be performed after cold rolling.

[0106] In the annealing step, annealing is performed while controlling the atmosphere in the heating furnace as described above.

[0107] The galvanizing step is performed, for example, by immersing in a hot-dip galvanizing bath. The hot-dip galvanizing treatment may be performed according to a conventional method, and the coating weight per one side is adjusted to be within the above range.

[0108] After the galvanizing treatment, the galvanized steel sheet may be subjected to an alloying treatment as required. In this case, the galvanized steel sheet may be kept at a temperature range of 450 to 580° C. for about 1 second to about 60 seconds.

[0109] Example

[0110] Molten steel with the composition shown in Table 1 is melted in a converter. The composition is mass %, and the remainder is Fe and inevitable impurities. The steel billet is heated to 1200°C and made into a hot-rolled coil with a thickness of 2.8 mm under the conditions of a finishing temperature of 840°C and a coiling temperature of 550°C. The hot-rolled coil is made into a cold-rolled steel sheet with a thickness of 1.4 mm at a cold rolling rate (reduction rate) of 50%. The cold-rolled steel sheet is annealed by an annealing treatment in an annealing furnace atmosphere under the conditions described in Table 2, and is cooled to 520°C under the conditions of an average cooling rate of 3°C / second to 600°C, and after retention for 50 seconds, galvanized to produce a high-strength hot-dip galvanized steel sheet.

[0111]

[0112] Samples were cut from the plated steel sheets obtained above, and the appearance was visually observed to evaluate the plating properties (surface properties), and the plating characteristics were evaluated. In addition, a tensile test was performed to measure the tensile strength (TS). The evaluation method is as follows.

[0113] (1) Oxygen content in the surface of the steel sheet within 100 μm from the surface of the base steel sheet to the center of the thickness immediately below the coating

[0114] In order to measure the oxygen content just below the coating, only the coating is peeled off using hydrochloric acid or alkaline solution to which an inhibitor is added so as not to dissolve the base steel, and then the oxygen content is measured using the "pulse furnace-infrared absorption method". However, it is necessary to subtract the oxygen content contained in the original material (i.e., the steel plate before annealing). Therefore, in the present invention, the surface layer of both sides of the high-strength steel plate after continuous annealing is ground by more than 100 μm, and the oxygen concentration in the steel is measured, and the measured value is set as the oxygen content OH contained in the original material. In addition, the oxygen concentration in the steel of the entire high-strength steel plate in the plate thickness direction after continuous annealing is measured, and the measured value is set as the oxygen content OI after oxidation. Using the oxygen content OI of the steel plate after oxidation obtained in this way and the oxygen content OH originally contained in the original material, the difference between OI and OH (=OI-OH) is calculated, and then converted into the amount per unit area of ​​a single side, and the value thus obtained (g / m 2 ) as the oxygen content.

[0115] Furthermore, a sample piece of 10 mm × 10 mm size was cut from the cross section after the coating was peeled off, and after being embedded in a resin, the sample was mirror-polished to prepare a sample for cross-sectional observation. Using SEM, under the condition of 5000 times, 5 fields of view were observed for each level of the cross section of 20 μm in the width direction, and the maximum length (μm) of the internal oxide in each observation field and the number of internal oxides with a length of more than 1.0 μm were measured, and the average value was taken as the maximum length of the internal oxide at that level and the number of internal oxides with a length of more than 1.0 μm. At this time, in the calculation of the number of internal oxides, only oxides with an oxide width of more than 0.1 μm were taken as the object.

[0116] (2) Surface properties (appearance)

[0117] The appearance of the manufactured hot-dip galvanized steel sheet was visually observed, and samples with no non-plating defects were marked as "○", samples with non-plating defects were marked as "×", and samples with no non-plating defects but uneven appearance of the plating layer were marked as "△". It should be noted that non-plating defects refer to areas where the plating layer is not present and the steel sheet is exposed at a level of 50 μm or more in terms of diameter.

[0118] The obtained results are shown in Table 2.

[0119] (3) Coating adhesion

[0120] [Alloyed hot-dip galvanized steel sheet]

[0121] In this embodiment, a transparent tape is pressed on the processing part of the hot-dip galvanized steel sheet bent 90° to transfer the peeling material to the transparent tape, and the amount of peeling material on the transparent tape is obtained as the Zn count number by the fluorescent X-ray method. The measurement conditions are set as a mask diameter of 30 mm, an acceleration voltage of 50 kV for fluorescent X-rays, an acceleration current of 50 mA, and a measurement time of 20 seconds. In particular, considering the possibility of uneven adhesion (deviation) within the surface, for any range of 6 m in the length direction of the manufactured hot-dip galvanized steel sheet, the adhesion is measured at 5 locations (a total of 30 locations) at 1 / 4 position, 1 / 2 position (center position), 3 / 4 position and 50 mm position from the end edge of the steel sheet every 1 m in the length direction of the coil, and the evaluation of the plating property is performed according to the following criteria based on the highest Zn count. In the present invention, the following grades ◎ or 0 are qualified.

[0122] ◎(Qualified, better): Zn count is less than 6000.

[0123] ○ (qualified, excellent): Zn count is 6000 or more and less than 8000.

[0124] × (failure): The Zn count is 8,000 or more.

[0125] [Unalloyed hot-dip galvanized steel sheet]

[0126] The coating adhesion of hot-dip galvanized steel sheets is evaluated by ball impact test. Under the conditions of ball weight of 2.8kg and drop height of 1m, the steel sheet is mounted on a mold with 3 / 8 and 1 / 2 inch holes, and then the ball impact test is performed. The processed part is tape-peeled and the coating peeling is visually determined. The following reference symbols are used. Here, less than 1mm is considered 2 The peeling is set as micro peeling, and 1mm 2 The above results are defined as peeling.

[0127] ◎ (Qualified, Better): No peeling of the coating under any conditions

[0128] ○ (Qualified, Excellent): Slight peeling at 3 / 8 inch diameter

[0129] △ (Unqualified): There is peeling at 3 / 8 inch diameter, and no coating peeling at 1 / 2 inch diameter

[0130] × (Unqualified): Plating peels off under any condition

[0131] (4) Corrosion resistance after processing

[0132] The same processing as the coating peeling resistance test was performed to prepare a test piece without tape peeling. The degreasing agent: FC-E2011, the surface conditioner: PL-X and the chemical conversion treatment agent: PALBOND (registered trademark) PB-L3065 manufactured by Japan Parkerizing Co., Ltd. were used. The chemical conversion treatment coating adhesion amount was 1.7 to 3.0 g / m under the following standard conditions. 2 The chemical conversion treatment is carried out in a manner.

[0133] <Standard conditions>

[0134] Degreasing process: Processing temperature is 40°C and processing time is 120 seconds

[0135] ·Spray degreasing and surface conditioning process: pH 9.5, treatment temperature room temperature, treatment time 20 seconds

[0136] Chemical conversion treatment process: The temperature of the chemical conversion treatment liquid is 35°C and the treatment time is 120 seconds

[0137] The surface of the test piece subjected to the chemical conversion treatment was subjected to electrodeposition coating using V-50 electrodeposition coating manufactured by Nippon Paint Co., Ltd. so as to have a film thickness of 25 μm, and was subjected to the following corrosion test.

[0138] <Salt spray test (SST)>

[0139] For the alloyed hot-dip galvanized steel sheet of the above-mentioned test piece that has been subjected to chemical conversion treatment and electroplating coating, a cutting defect reaching the coating is given on the surface of the bent portion by a cutter, and for the hot-dip galvanized steel sheet, a cutting defect reaching the coating is given on the ball impact portion by a cutter, and then the test piece is subjected to a 240-hour salt spray test using a 5 mass % NaCl aqueous solution in accordance with the neutral salt spray test specified in JIS Z2371:2000, and then a tape peeling test is performed on the cross-cut defect portion to measure the maximum total peeling width including the cutting defect portion. According to the following reference marking symbols (◎, ○, ×). When the maximum total peeling width is less than 2.0 mm, the corrosion resistance in the salt spray test can be evaluated as good.

[0140] ◎: The maximum total expansion width from the cutting defect is less than 2.0 mm (good)

[0141] ○: The maximum total width of expansion from the cutting defect exceeds 2.0 mm and is less than 2.5 mm (acceptable)

[0142] ×: The maximum total expansion width from the cutting defect exceeds 2.5 mm (unqualified)

[0143] (5) Tensile test

[0144] A JIS No. 5 tensile test piece (JIS Z2201) was cut from the plated steel sheet in a direction perpendicular to the rolling direction, and a tensile test was performed at a constant tensile speed (crosshead speed) of 10 mm / min. The tensile strength was set to the value obtained by dividing the maximum load in the tensile test by the cross-sectional area of ​​the parallel portion of the test piece at the initial stage. The plate thickness in the calculation of the cross-sectional area of ​​the parallel portion used the plate thickness value including the coating thickness.

[0145] (6) Analysis method of furnace gas

[0146] The furnace gas was collected from the annealing furnace and the SO2 and HCl were quantified by ion chromatography. The analysis was performed three times and the average value was taken as the furnace gas concentration.

[0147]

[0148] As is clear from Table 2, the hot-dip galvanized steel sheet manufactured by the method of the present invention is a high-strength steel sheet containing a large amount of easily oxidizable elements such as Si and Mn, but has excellent coating adhesion and good coating appearance. On the other hand, in the comparative examples, at least one of the coating appearance, coating adhesion, and tensile strength is poor.

[0149] Industrial Applicability

[0150] The high-strength hot-dip galvanized steel sheet of the present invention has excellent coating appearance and coating adhesion, and can be used as a surface-treated steel sheet for making the body of an automobile lighter and stronger. In addition, in addition to automobiles, it can also be used in a wide range of fields such as home appliances and building materials as a surface-treated steel sheet that imparts rust resistance to the original steel sheet.

Claims

1. A method for producing a high-strength hot-dip galvanized steel sheet, comprising producing a steel sheet having a coating weight of 20 g / m2 per single surface on the surface of the steel sheet containing, by mass%, C: 0.08% or more and 0.25% or less, Si: 0.1% or more and less than 2.0%, Mn: 1.5% or more and 3.5% or less, P: 0.02% or less, S: 0.01% or less, Al: 0.10% or less, N: 0.006% or less, a mass ratio of Si to Mn (Si / Mn) of 0.25 or more, and the balance being Fe and unavoidable impurities. 2 Above and 120g / m 2 A method for coating a high-strength hot-dip galvanized steel sheet with a zinc layer, wherein: When a steel sheet is subjected to annealing and hot-dip galvanizing treatment in a continuous hot-dip galvanizing facility, the maximum temperature T of the steel sheet in the annealing heating furnace is 900° C. or less, the dew point X (° C.) of the atmosphere in the heating furnace within a temperature range of 700° C. or more and T° C. or less of the steel sheet temperature is controlled to be above the dew point calculated using the following formula (1), and the atmosphere in the heating furnace contains, in addition to 3.0% by volume or more and 20.0% by volume or less of hydrogen, at least one of 0.1% by volume ppm or more and 3.0% by volume ppm of SO2 and 0.5% by volume ppm or more and 10.0% by volume ppm of HCl, with the remainder being nitrogen and impurities, Dew point X ≥ (-50 + [Si mass %] × (T-600) / 30 + [Mn mass %] × (T-600) / 25) … (1) Here, Si mass % is the mass % of Si in the component composition of the steel plate, and Mn mass % is the mass % of Mn in the component composition of the steel plate.

2. The method for manufacturing a high-strength hot-dip galvanized steel sheet according to claim 1, wherein: The steel plate further contains, in terms of mass %, one or more selected from the following groups A to E: Group A: one or more of Ti, Nb, V and Zr with a total content of less than 0.2%; Group B: one or more of Mo, Cr, Cu and Ni in a total amount of 0.01% to 0.5%; Group C: B with a value of more than 0.0003% and less than 0.005%; Group D: one or more of Sb and Sn in a total amount of 0.001% or more and 0.2% or less; Group E: One or more of Ca, Mg, and REM in an amount of 0.0001% to 0.0005% in total.

3. A high-strength hot-dip galvanized steel sheet, comprising, by mass%, C: 0.08% to 0.25%, Si: 0.1% to less than 2.0%, Mn: 1.5% to 3.5%, P: 0.02% to less than 0.01%, S: 0.01% to less than 0.10%, N: 0.006% to less than 0.006%, a mass ratio of Si to Mn (Si / Mn) of 0.25 or more, and the balance consisting of Fe and unavoidable impurities, and having a coating weight of 20 g / m2 per single surface on the surface of the steel sheet 2 Above and 120g / m 2 The following galvanized layers, The oxygen content of the steel sheet surface within 100 μm from the surface of the base steel sheet to the center of the sheet thickness immediately below the galvanized layer is 0.030 g / m per single side. 2 Above and 0.40g / m 2 Hereinafter, the maximum length of the oxides existing in the surface portion of the steel plate is 6.0 μm or less, and the number of oxides having a length of 1.0 μm or more existing in the surface portion of the steel plate is 20 or less per 100 μm length of the surface portion of the steel plate in the width direction of the steel plate.

4. The high-strength hot-dip galvanized steel sheet according to claim 3, wherein: The steel plate further contains, in terms of mass %, one or more selected from the following groups A to E: Group A: one or more of Ti, Nb, V and Zr with a total content of less than 0.2%; Group B: one or more of Mo, Cr, Cu and Ni in a total amount of 0.01% to 0.5%; Group C: B with a value of more than 0.0003% and less than 0.005%; Group D: one or more of Sb and Sn in a total amount of 0.001% or more and 0.2% or less; Group E: One or more of Ca, Mg, and REM in an amount of 0.0001% to 0.0005% in total.

Citation Information

Patent Citations

  • High-strength galvannealed steel sheet with fine appearance, manufacturing method therefor and manufacturing facility

    JP2006233333A

  • Protection device

    JP2014102901A

  • Method for manufacturing steel sheet products with a metal protective layer formed by hot-dip plating.

    JP2014525986A